Description of a soft‐bodied invertebrate with microcomputed tomography and revision of the genus Chtonobdella (Hirudinea: Haemadipsidae). (11th January 2016) - Tessler, Michael; Barrio, Amalie; Borda, Elizabeth; Rood‐Goldman, Rebecca; Hill, Morgan; Siddall, Mark E.
Abstract : Two‐jawed (duognathous) terrestrial leeches in the Haemadipsidae are major pests across their wide geographic range, represented by numerous endemic species in Australia and across many islands in the Indian and Pacific Oceans. However, haemadipsid taxonomy, based largely on externally visible characters, remains in conflict with phylogenetic relationships. We capitalize on the power of microcomputed tomography ( μ CT), allowing for the first description of an extant soft‐bodied species – Chtonobdella tanae sp. n. – using this technology. Several fixation strategies for soft‐bodied invertebrates in μ CT scanning applications are also evaluated. Expanding on prior work, higher taxonomy of duognathous haemadipsids also was evaluated with phylogenetic analyses of DNA sequence data. Whereas monophyly of duognathous leeches was supported, substantial conflict remained with respect to named genera. Consequently, the genus Chtonobdella was revised to include all duognathous leech species previously distributed in 31, mostly monotypic genera.